Properties of Fluorescent Far-Red Anti-TNF Nanobodies - Gorshkova, Ekaterina N. (Antibodies (Basel), 2018)
Upregulation of the expression of tumor necrosis factor (TNF-α, TNF) has a significant role in the development of autoimmune diseases. The fluorescent antibodies binding TNF may be used for personalized therapy of TNF-dependent diseases as a tool to predict the response to anti-TNF treatment. We generated recombinant fluorescent proteins consisting of the anti-TNF module based on the variable heavy chain (VHH) of camelid antibodies fused with the far-red fluorescent protein Katushka (Kat). Two types of anti-TNF VHH were developed: one (BTN-Kat) that was bound both human or mouse TNF, but did not neutralize their activity, and a second (ITN-Kat) that was binding and neutralizing human TNF. BTN-Kat does not interfere with TNF biological functions and can be used for whole-body imaging. ITN-Kat can be evaluated in humanized mice or in cells isolated from humanized mice. It is able to block human TNF (hTNF) activities both in vitro and in vivo and may be considered as a prototype of a theranostic agent for autoimmune diseases.